New International Order In Light Of The Emergence Of Rising Powers (China's Model 1991-2015) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The study aimed highlight China's status as agents active and influential in the New International Order, the study curriculum systems analysis theory,  theory was used because of the ability of this approach to highlight the role that China can play and change the features of future the international system depend on growing military, economic and political power. The study answered central question "What is the role of China in the new international order in the light of the holdings of the ingredients to play that role, and what is the future of the international political system in light of the emergence of China's emerging powers"?. The study dealt with it in economic terms, where China is experiencing unprecedented growth, and political issue. China has completed the construction of its own power, regional, and striving for years to build its international profile, a strong candidate to contribute to the possibility of change in the international order form. The study concluded main general results: That China was able to secure the site at the global and regional levels, allowing the maximum extent possible to implement the main necessary modernization and reform plans. And the establishment of wide cooperation with Asia and Southeastern Asia countries in development of science, technology and economic. يتجسد هدف الدراسة في تسليط الدور على مكانة الصين كقطب  دولي فاعل ومؤثر في الساحة الدولية وذلك من خلال استخدام منهج تحليل النظم نظراً لقدرة هذا المنهج على تسليط الضوء على الدور الذي يمكن أن تلعبه الصين في تغير ملامح مستقبل النظام الدولي في ظل تنامي قوتها العسكرية والاقتصادية والسياسية. وحاولنا الإجابة على الأسئلة المحورية للدراسة وخصوصاً دور الصين في النظام الدولي الجديد في ظل ما تمتلكه من مقومات للعب هذا الدور؟ وكذلك ما هو مستقبل النظام الدولي والعلاقات الدولية في ظل بروز الصين كقطب فاعل ومؤثر, عالجت الدراسة أيضاً ذلك من خلال الناحية الاقتصادية حيث تشهد الصين معدلات نمو مرتفعة وغير مسبوقة, ومن الناحية السياسية حيث انتهت الصين من بناء قوتها الذاتية والإقليمية وأنتهجت لتوطيد مكانتها الدولية. وقد خلصت الدراسة إلى أن الصين قد استطاعت احتلال موقع متميز على المستويين الإقليمي والدولي بما أتاح لها أقصى حد لتنفيذ خططها في التحديق والاطلاع على كافة الصعد. يضاف إلى ما سبق سعي الصين إلى إقامة وتطوير تعاون اقتصادي وعلمي وتكنولوجي واسع النطاق مع مختلف الدول والتكتلات الاقتصادية بما يخدم هدف الصين المتمثل بأن تكون أحد أهم الأقطاب على الساحة الدولية.